2019
DOI: 10.3390/polym11030531
|View full text |Cite
|
Sign up to set email alerts
|

Development and Investigation of Lanthanum Sulfadiazine with Calcium Stearate and Epoxidised Soyabean Oil as Complex Thermal Stabilizers for Stabilizing Poly(vinyl chloride)

Abstract: Lanthanum sulfadiazine (LaSD) was synthesized from sulfadiazine and lanthanum nitrate using water as solvent under alkaline conditions, and was used as a novel rare earth thermal stabilizer to stabilize poly(vinyl chloride) (PVC). The structure of LaSD was characterized by elemental analysis (EA), Fourier transform infrared spectroscopy (FTIR) and thermo- gravimetric analysis (TGA). The influence of lanthanum sulfadiazine with calcium stearate (CaSt2) and epoxidized soybean oil (ESBO) on stabilizing PVC was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The first stage is mainly attributed to dehydrochlorination by the removal of hydrogen chloride from the PVC main chain, thus forming a conjugated polyene structure. The second stage is mainly attributed to the fracture of conjugated polyene structures to form small molecular weight linear or cyclic hydrocarbons, and finally tar formation [ 25 , 26 ]. In addition, it was observed that there is a substage in the first stage of the PVC, indicating the existence of different events in this stage, suggesting a complex dehydrochlorination mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The first stage is mainly attributed to dehydrochlorination by the removal of hydrogen chloride from the PVC main chain, thus forming a conjugated polyene structure. The second stage is mainly attributed to the fracture of conjugated polyene structures to form small molecular weight linear or cyclic hydrocarbons, and finally tar formation [ 25 , 26 ]. In addition, it was observed that there is a substage in the first stage of the PVC, indicating the existence of different events in this stage, suggesting a complex dehydrochlorination mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the tested formula uses high Ca/Zn ratios. As reported in the literature (Balköse et al, 2001;Ye et al, 2019), a high Ca/Zn ratio has advantages in long stability times but is lacking in initial color. The recommended Ca/Zn ratio in a mixed metal formulation is 0.25 to 4.00 with the lower and higher ratios being prioritized for initial color and long-term stability, respectively (Balköse et al, 2001).…”
Section: Stabilization Mechanismmentioning
confidence: 93%
“…The disadvantage of organic thermal stabilizers are their poor stability ( Guangbao et al., 2020 ). The second group, which has been industrialized and well applied in PVC production, includes salts or carboxylates of lead, tin, or mixed metals ( Ye et al., 2019 ). Lead salts are known as the oldest thermal stabilizer ( Schiller, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the traditional thermal stabilizers, such as lead/cadmium salts and organotin, pose health and environmental hazards, leading to regulations such as EU 76/769/EEC, WEEE, and RoHS that require the use of non-toxic, environmentally friendly, and efficient thermal stabilizers [ 8 ]. Thermal stabilizers of β-diketone compounds, zinc stearate, and LDHs show great potential as practical alternatives [ 4 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%